Design of a Transdisciplinary Methodology for the Identification and Characterisation of Industrial Landscapes - Alba-Dorado, María Isabel (MDPI, 2022)
Today, the industrial landscape constitutes an extraordinarily complex phenomenon, the study of which has been approached belatedly by the scientific community in general. This has given rise to a situation of conceptual and methodological insufficiency in the field of landscape study, making necessary both a reconsideration of the ways these studies have been approached to date and the development of a methodological framework that takes into account the specific nature of these landscapes. With this in mind, the objective of this article is to present a specific methodology for the identification and characterisation of industrial landscapes based on both their heritage and cultural considerations. The methodology contemplates an initial in-depth study of both the landscapes in question and the most relevant methodological trends applied to landscape study, in an effort to ascertain to what extent these methodological approaches respond to the needs of the study. On the basis of the results obtained, this article attempts to make an advance in the contribution of methodological improvements and innovations that materialise in the design of an industrial landscape identification and characterisation methodology, that contemplates a holistic, integrational approach that operates across the various dimensions attributable to these landscapes and advocates a transdisciplinary approach to the study of the same.
Keywords: Paisaje; Industrial heritage; Industrial landscape; Post-industrial sites; Transdisciplinary methodology; Landscape identification; Landscape characterisation